Intra-arterial thrombolysis in 24 consecutive patients with internal carotid artery T occlusions. Issue 6 (1st June 2003) - Arnold, M; Nedeltchev, K; Mattle, H P; Loher, T J; Stepper, F; Schroth, G; Brekenfeld, C; Sturzenegger, M; Remonda, L
Abstract : Objectives: To determine the safety, efficacy, and predictors of favourable outcome of intra-arterial thrombolysis in acute stroke attributable to internal carotid "T"occlusion Methods: The authors analysed 24 consecutive patients with T occlusions of the internal carotid artery treated by local intra-arterial thrombolysis using urokinase. Results: The median baseline National Institutes of Health Stroke Scale was 19. The average time from symptom onset to treatment was 237 minutes. Four patients (16.6%) had a favourable (modified Rankin Scale score (mRS⩽2)) and 10 patients (41.7%) a poor outcome (mRS 3 or 4) after three months. Ten patients (41.7%) died. One symptomatic intracerebral haemorrhage (4.2%) occurred. Partial recanalisation of the intracranial internal carotid artery was achieved in 15 (63%), of the middle cerebral artery in four (17%), and of the anterior cerebral artery in eight patients (33%). Complete recanalisation never occurred. Sufficient leptomeningeal collaterals as seen on arteriography (p=0.02) and age <60 years (p=0.012) were the only predictors of favourable clinical outcome. Conclusions: Acute stroke attributable to carotid T occlusion remains a condition with a generally poor prognosis even when intra-arterial thrombolysis is performed. Favourable outcome was seen only in patients with sufficient leptomeningeal collaterals.